5-Hydroxytryptamine1a receptors on tumour cells induce immune evasion in lung adenocarcinoma patients with depression via autophagy/pSTAT3. (June 2019) - Liu, Yi; Zhang, Hao; Wang, ZhiYong; Wu, Pin; Gong, Wei
Abstract: Background: Cancer patients frequently suffer from fatigue and depression. Dysregulation of the immune system, tumour recurrence and metastasis are more common in cancer patients with depression. 5-Hydroxytryptamine (5-HT), a neurotransmitter, contributes to immune evasion in lung adenocarcinoma patients by activating 5-HTRs, but the mechanism for this phenomenon is still unclear. In this study, we examined the function of 5-HT1a receptors (5-HT1aRs) in immune evasion in a mouse model and in samples from lung adenocarcinomas patients. Experimental design: Sixty-four human lung adenocarcinoma patients with depression and 64 lung adenocarcinoma patients without depression were recruited for this study. The expression of 5-HT receptors on lung adenocarcinoma cells from tumour tissues were detected by using immunohistochemistry (IHC) and fluorescence-activated cell sorting (FACS). The depression models were established in vitro and in vivo . The effects of immunosuppression were evaluated by testing the function of cytotoxic lymphocyte (CTLs) and Tregs, measuring tumour weight or volume, assessing the survival of mice and staining of tissues by IHC. Changes in the expression of immunoregulatory factor genes were assessed to elucidate the mechanism of immune evasion induced by the 5- hydroxytryptamine receptor (HTRs). Results: Higher levels of 5-HT, increased expression of 5-HT1Rs and decreased overall survival were observed in lung adenocarcinomas patients with depression compared with those without depression. Moreover, 5-HT1aR, a critical factor for increasing the number of CD4 + CD25 + Foxp3 + Treg cells and decreasing the ratio of Th1/Th2 cells, which suggested immune system dysregulation. In addition, expression of 5-HT1aR on tumour cells was also negatively associated with CTL activity in both peripheral blood and tumour infiltrating lymphocytes. In a depressive state, 5-HT1aR activates p-signal transducer and activator of transcription 3 (STAT3) and autophagy, and programmed death ligand-1, a downstream gene of autophagy/p-STAT3 signalling, mediates an immunosuppressive environment. Moreover, in both the mouse model and lung adenocarcinoma patients, the activation of 5HT1aR and the elevated tumour autophagy/p-STAT3 axis were associated with reduced overall survival. Conclusions: The 5-HT1aR/autophagy/p-STAT3 axis influences both tumour cells and immune cells, resulting in immunosuppression in lung adenocarcinomas patients with depression. Highlights: 5-HT1aR (5-hydroxytryptamine1a receptor) in tumours cells was higher from lung adenocarcinomas patients in depression. The higher expression of 5-HT1aR in tumour cells was associated with worse overall survival. 5HT1aR could influence both tumour cells and T-cells to create an immunosuppressive environment though activation of autophagy/p-STAT3-programmed death ligand-1 signal under depression stress.